Immunological differences between primary and metastatic breast cancer. (10th September 2018) - Szekely, B; Bossuyt, V; Li, X; Wali, V B; Patwardhan, G A; Frederick, C; Silber, A; Park, T; Harigopal, M; Pelekanou, V; Zhang, M; Yan, Q; et al.
Abstract: Background: Little is known about how the immune microenvironment of breast cancer evolves during disease progression. Patients and methods: We compared tumor infiltrating lymphocyte (TIL) count, programmed death-ligand 1 (PD-L1) protein expression by immunohistochemistry and mRNA levels of 730 immune-related genes using Nanostring technology in primary and metastatic cancer samples. Results: TIL counts and PD-L1 positivity were significantly lower in metastases. Immune cell metagenes corresponding to CD8, T-helper, T-reg, Cytotoxic T, Dendritic and Mastoid cells, and expression of 13 of 29 immuno-oncology therapeutic targets in clinical development including PD1, PD-L1, and CTLA4 were significantly lower in metastases. There was also coordinated down regulation of chemoattractant ligand/receptor pairs (CCL19/CCR7, CXCL9/CXCR3, IL15/IL15R), interferon regulated genes (STAT1, IRF-1, -4, -7, IFI-27, -35), granzyme/granulysin, MHC class I and immune proteasome (PSMB-8, -9, -10) expression in metastases. Immunotherapy response predictive signatures were also lower. The expression of macrophage markers (CD163, CCL2/CCR2, CSF1/CSFR1, CXCR4/CXCL12), protumorigenic toll-like receptor pathway genes (CD14/TLR-1, -2, -4, -5, -6/MyD88), HLA-E, ecto-nuclease CD73/NT5E and inhibitory complement receptors (CD-59, -55, -46) remained high in metastases and represent potential therapeutic targets. Conclusions: Metastatic breast cancers are immunologically more inert than the corresponding primary tumors but some immune-oncology targets and macrophage and angiogenesis signatures show preserved expression and suggest therapeutic combinations for clinical testing.